2022
DOI: 10.3390/plants11192607
|View full text |Cite
|
Sign up to set email alerts
|

A Rhizobacterium, Streptomyces albulus Z1-04-02, Displays Antifungal Activity against Sclerotium Rot in Mungbean

Abstract: Sclerotium rot causes damping-off and stem rot in seedlings and mature mungbeans, which negatively impacts cultivation. The use of a rhizobacterium to control soil-borne diseases is an alternative method to the excess use of synthetic fungicides; therefore, this study aims to screen rhizosphere actinobacteria with fungicidal activities against Sclerotium rolfsii, the pathogen that causes sclerotium rot in mungbeans. Primary screening showed that the Streptomyces sp. isolate Z1-04-02 displayed the highest effec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 49 publications
0
3
0
Order By: Relevance
“…These enzymes are responsible for catalyzing the hydrolysis of chitin and β-1,3-glucan, which are the major structural components of fungal cell walls. Accumulated data indicate that chitinases and β-1,3-glucanases produced by biocontrol microbes and plants can inhibit fungal growth [48,49]. The study conducted by Arora et al [45] showed that the chitinase and β-1,3-glucanase produced by Fluorescent pseudomonad can inhibit the growth of Rhizoctonia solani.…”
Section: Discussionmentioning
confidence: 99%
“…These enzymes are responsible for catalyzing the hydrolysis of chitin and β-1,3-glucan, which are the major structural components of fungal cell walls. Accumulated data indicate that chitinases and β-1,3-glucanases produced by biocontrol microbes and plants can inhibit fungal growth [48,49]. The study conducted by Arora et al [45] showed that the chitinase and β-1,3-glucanase produced by Fluorescent pseudomonad can inhibit the growth of Rhizoctonia solani.…”
Section: Discussionmentioning
confidence: 99%
“…These enzymes are responsible for catalyzing the hydrolysis of chitin and β-1,3-glucan, which are the major structural components of fungal cell walls. Accumulated data indicate that chitinases and β-1,3-glucanases produced by biocontrol microbes and plants can inhibit fungal growth ( Li et al, 2021 ; Ruangwong et al, 2022 ). The study conducted by Arora et al (2007) showed that the chitinase and β-1,3-glucanase produced by fluorescent pseudomonads can inhibit the growth of Rhizoctonia solani .…”
Section: Discussionmentioning
confidence: 99%
“…Oryza sativa (Rice) -Produce indole-3-acetic acid -Improves adventitious roots formation -Siderophore production [57] Streptomyces olivaceoviridis Triticum aestivum (Wheat) -Accelerates the emergence of adventitious roots -Enhances biosynthesis of gibberellin -Produces cytokinins [58] when compared to that of S. atrovirens, and therefore different effects of these species on plant growth were recorded. Similarly, Streptomyces albulus revealed that due to its antifungal activity against sclerotium rot in mungbean, it has the potential as a biocontrol agent [18]. Likewise, Streptomyces alfalfae XN-04 creates several siderophores, such as coelichelin, enterobactin, and mirubactin, which are influential plant growth promoters and disease suppressants [19].…”
Section: Streptomyces Hygroscopicusmentioning
confidence: 99%